Concept of consent: universal model of concerted communication (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The author of the article refers to the wide interpretation of the concept of consent, which represents the ethical concepts of effective communication, belongs to the important characteristics of the behaviour of the individual in society. Thescientific consideration of the concept from the standpoint of language, the clarification of its cognitive and pragmatic features, makes it possible to identify one of many motivational forms of the mental representation of knowledge about concerted communication.In the perception of the concept, we could find a pragmatic approach, such as: “understanding, consensus, agreement, confirmation, assignment”. By the analysis of the vocabulary definitions, we conclude that the content structure of the concept has etymologically inherited and modern interpretations. Firstly, the concept of consent is etymologically correlated with the logical-philosophical and ethical categories and concepts, and imply peace, goodness, truth, the ability of the interlocutor to the desired actions. From etymological preconditioned interpretation of “peaceful” it was inherited meaning “harmony, friendship, order, agreement, consistency”. Secondly, over time, the basic constant of the concept “peaceful” was supplemented, reflecting the modern ethno-linguistic consciousness of Ukrainians.In the perception of the concept, we could find a pragmatic approach, such as: “understanding, consensus, agreement, confirmation, assignment”. Therefore, in contemporary dictionaries, the concept of consent is widely interpreted, enabling its semantic interpretation in the plane of cooperation, compromise, avoidance and assignment.
Keywords: concept of consent; concerted communication; etymological and modern linguospecificity; semantic interpretation